Analytic geometry - De La Cruz, Perla S. (Quezon City, Philippines : C & E Publishing Inc., 2013)
Analytic geometry is a college textbook intended for a semester-long introductory course in the subject. It was developed in response to a long-felt need for an up-to-date and locally authored textbook. Its classical approach aims to prepare students of engineering, sciences, and other related courses for college-level calculus... -- Preface
Preface ix -- Chapter 1: Preliminary concepts -- Chapter 2: Lines -- Chapter 3: Circles -- Chapter 4: Conic sections -- Chapter 5: Simplification of equations -- Chapter 6: Algebraic curves -- Chapter 7: The polar coordinate system -- Bibliography -- Appendices -- About the authors
Includes bibliographical references.
Keywords: GEOMTRY, ANALYTIC